2018
DOI: 10.1002/advs.201800559
|View full text |Cite
|
Sign up to set email alerts
|

A Dual‐Salt Gel Polymer Electrolyte with 3D Cross‐Linked Polymer Network for Dendrite‐Free Lithium Metal Batteries

Abstract: Lithium metal batteries show great potential in energy storage because of their high energy density. Nevertheless, building a stable solid electrolyte interphase (SEI) and restraining the dendrite growth are difficult to realize with traditional liquid electrolytes. Solid and gel electrolytes are considered promising candidates to restrain the dendrites growth, while they are still limited by low ionic conductivity and incompatible interphases. Herein, a dual‐salt (LiTFSI‐LiPF6) gel polymer electrolyte (GPE) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
121
0
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(137 citation statements)
references
References 44 publications
1
121
0
8
Order By: Relevance
“…Hence, the local current density is significantly increased, which leads to uneven Li deposition. It has been reported that the localcurrent density can be reduced by using high-surface-area current collectors [38][39][40][41][42][43][44][45][46][47], which results in a significantly improved cycling performance. Hence, only a uniform and strong artificial SEI, instead of native SEI, can alter the fundamental self-amplifying behavior of dendritic growth [2,26,[48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the local current density is significantly increased, which leads to uneven Li deposition. It has been reported that the localcurrent density can be reduced by using high-surface-area current collectors [38][39][40][41][42][43][44][45][46][47], which results in a significantly improved cycling performance. Hence, only a uniform and strong artificial SEI, instead of native SEI, can alter the fundamental self-amplifying behavior of dendritic growth [2,26,[48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission from Ref. , Copyright 2018 Wiley‐VCH. b) Mechanism of the LiPF 6 ‐induced polymerization of DOL.…”
Section: Blended‐salt Electrolytes For Battery Chemistries “Beyond LImentioning
confidence: 99%
“…Similarly, Li and co-workers designed a novel dual-salt lithium bis(trifluoromethanesulfonyl)imide–lithium hexafluorophosphate (LiTFSI-LiPF 6 ) GPE with a 3D cross-linked polymer network [ 162 ] ( Figure 17 b). The 3D cross-linked polymer network by poly(ethylene glycol) diacrylate (PEGDA) and ethoxylated trimethylolpropane triacrylate was formed using dual-salts.…”
Section: Hybridized Use Of Electrolytes and Separators: Solid And mentioning
confidence: 99%
“…( b ) Step process for in situ polymerization of GPE. Reprinted with permission from [ 162 ]. Copyright (2018) John Wiley and Sons.…”
Section: Figurementioning
confidence: 99%